Children, education, labor and land: In the long run and short - Talia Bar; Kaushik Basu (Cornell University, Center for Analytical Economics (CAE), 2008)
The paper uses an overlapping generations model to examine the effects of an increase in a household's land ownership on child labor. Consistent with previous studies, it is found that small increases in land lead to increased child labor. However, as land continues to increase child labor declines. Further, even when an increase in land ownership causes an immediate rise in child labor, there are contexts where long-run child labor (that is aggregated over progenies) declines.
Keywords: 330; Grundbesitz; Kinderarbeit; Overlapping Generations; Theorie